Chaotic transport in symplectic maps: applications in plasma - Silva, Matheus Palmero (2023)
Chaotic transport is related to the complex dynamical evolution of chaotic trajectories in Hamiltonian systems, which models various physical processes. In magnetically confined plasma, it is possible to qualitatively describe the configuration of the magnetic field via the phase space of suitable symplectic maps. These phase spaces are of mixed type, where chaos coexists with regular motion, and the complete understanding of the chaotic transport is a challenge that, when overcome, may provide further knowledge into the behaviour of confined fusion plasma. In this research, we focus our investigation on the properties of chaotic transport in mixed phase spaces of two symplectic maps that model the magnetic field lines of tokamaks under distinct configurations. The single-null divertor map, or Boozer map, models the field lines of tokamaks with poloidal divertors. The ergodic magnetic limiter map, or Ullmann map, models the magnetic configuration of tokamaks assembled with ergodic magnetic limiters. We propose two numerical methods developed to study and illustrate the differences between the transient behaviour of open field lines in both models while considering induced magnetic configurations that either enhance or restrain the escaping field lines. The first analysis shows that the spatial organisation of invariant manifolds creates fitting transport channels for the open field lines, influencing the average dynamical evolution in the selected magnetic configurations. The second identifies trajectories that widely differ from the average chaotic behaviour, specifically detecting the stickiness phenomenon, which can be related to additional confinement regions in the nearest surroundings of magnetic islands in the plasma edge. These analyses may, ultimately, assist in selecting optimal experimental parameters to achieve specific goals in tokamak discharges.